Des Powerpoints en chaînes. - Gustavo GOMEZ-MEJIA (Tic & Société)
On PowerPoint chain letters. Forms and circulation of Christian slideshows in Latin America – This article focuses on the forms and circulation of Powerpoint slideshows as digital supports for religious signs in Latin American space. A corpus of presentations sent by e-mail allows the author to analyze three main dimensions of the “religious chain” phenomenon. Firstly, the characteristics that such chains share with older postal practices nowadays remediated by on-screen e-mail services. Secondly, the modes in which Christian texts and imageries are reshaped by Powerpoint formats. Lastly, the ways in which such slideshows reflect the evolving landscape of beliefs in Latin America. Semiotic approaches contribute to the comprehension of both the cultural complexities of these ordinary objects and their mysterious circulation.